2006
DOI: 10.1182/blood-2006-05-023093
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of overactivated p38 MAPK can restore hematopoiesis in myelodysplastic syndrome progenitors

Abstract: The myelodysplastic syndromes (MDSs) are collections of heterogeneous hematologic diseases characterized by refractory cytopenias as a result of ineffective hematopoiesis. Development of effective treatments has been impeded by limited insights into any unifying pathogenic pathways. We provide evidence that the p38 MAP kinase is constitutively activated or phosphorylated in MDS bone marrows. Such activation is uniformly IntroductionThe myelodysplastic syndromes (MDSs) comprise a spectrum of stem-cell malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 48 publications
3
94
0
1
Order By: Relevance
“…Inhibition of p38MAPK activity was found to decrease apoptosis and stimulate GM colony formation in primary MDS progenitors, suggesting a role for p38MAPK in the pathogenesis of this syndrome. 37,27 However, our data indicate that inhibition of p38MAPK is not sufficient to restore final maturation or improve the clonogenic capacity of low-risk MDS hematopoietic progenitors ( Figure 3D, 3E). Moreover, CD34 + cells from low-risk MDS patients did not show elevated levels of phosphorylated p38MAPK compared to control cells ( Figure 3A, 3B).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Inhibition of p38MAPK activity was found to decrease apoptosis and stimulate GM colony formation in primary MDS progenitors, suggesting a role for p38MAPK in the pathogenesis of this syndrome. 37,27 However, our data indicate that inhibition of p38MAPK is not sufficient to restore final maturation or improve the clonogenic capacity of low-risk MDS hematopoietic progenitors ( Figure 3D, 3E). Moreover, CD34 + cells from low-risk MDS patients did not show elevated levels of phosphorylated p38MAPK compared to control cells ( Figure 3A, 3B).…”
Section: Discussionmentioning
confidence: 55%
“…27 Inhibition of p38MAPK activity resulted in decreased apoptosis and stimulated colony formation of primary MDS progenitors, indicating a role for p38MAPK in the pathogenesis of MDS. 27 To determine whether aberrant p38MAPK activation may be involved in the defective neutrophil differentiation observed in MDS primary progenitors, CD34…”
Section: Inhibition Of P38 Mapk Does Not Improve Maturation or Increamentioning
confidence: 99%
“…In addition, activation of p38 has been implicated in BM suppression in various pathological conditions, including aplastic anemia and myelodysplastic syndromes (118,175). Furthermore, recently, it was shown that mutation of the ATM gene and knockout of the FoxO3 gene induced premature senescence/exhaustion of HSCs (69,112,149).…”
Section: P38mentioning
confidence: 99%
“…Patients with other causes of anemia did not reveal activation. 33 Histological examination revealed that p38 was activated in hematopoietic progenitors of all three lineages. Immunohistochemical staining with an antibody against p38 MAPK revealed no significant differences between diseased samples and controls suggesting that p38 MAPK is overactivated but not overexpressed in MDS.…”
Section: P38 Mapk Is Constitutively Activated In Myelodysplastic Syndmentioning
confidence: 99%